Employee Performance Analysis Influenced by Leadership Style, Motivation and Work Discipline - Marselia Purnama; Adrian Hidayat; Tri Angreni (Komunitas Dosen Indonesia, 2021)
This study aims to examine and analyze employee performance analysis which is influenced by leadership style, motivation and work discipline. The analytical method used in this study is a survey research method. The sampling technique in this study used a questionnaire. Data analysis used multiple regression analysis. The results of this study note that the relationship of leadership style, motivation, and work discipline to employee performance. Beta value of leadership style 0.729 and 0.000 significance value <0.05. Leadership style has a significant relationship to employee performance. Beta value of motivation 0.191 and 0.028 significant value <0.05. Motivation has a significant relationship to employee performance. Beta value of work discipline 0.204 and 0.008 significance value <0.05. Work discipline has a significant relationship with employee performance. leadership style, motivation and work discipline have a significant relationship to employee performance together. The F statistic value is 57,258 with a significance of 0.000 < 0.05. Determination coefficient value 0.630